WORKSHOP PENGEMBANGAN ASESMEN NUMERASI BERBASIS HIERARCHICALCONTENT DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN 2 DAREK LOMBOK TENGAH - Astria, Fitri Puji; Affandi, Lalu Hamdian; Putri, Hikmah Ramdhani; Hidayati , Vivi Rachmatul; Hasnwati, Hasnawati (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
Numeracy is an important component in mathematics learning today, especially in the Independent Curriculum. Numeracy abilities include a person's knowledge and skills in using basic mathematical concepts in order to solve appropriate contextual problems. Based on the investigation, it is known that SDN 2 Darek still has a red report card (not yet achieved) in the numeracy domain. The teachers at SDN 2 Darek are still in the learning process in implementing differentiated learning, especially in mathematics learning. Teachers have not been able to develop a numeracy evaluation instrument that can provide an initial picture of student abilities and student learning needs. Based on the analysis of situations and problems, the aim of this service is to provide understanding and improve teachers' skills in compiling appropriate numeracy test instruments to detect students' initial difficulties and abilities by holding a hierarchical content-based assessment development workshop in the independent curriculum for elementary school students. The workshop material provided to SDN 2 Darek teachers includes the following things, namely: 1) assessment concepts in the independent curriculum, 2) numeracy assessments and their follow-up, 3) preparation of numeracy assessments based on hierarchical content. The stages in this workshop activity are starting from the preliminary study (coordination stage), preparation stage, implementation stage and evaluation and reporting stage. This workshop activity was carried out at SDN 2 Darek Central Lombok on August 21 2024. Based on the results of the pre-test and post-test, there was an increase in the understanding of the workshop participant teachers regarding the concept of assessment in the Merdeka curriculum and based on the results of the participants' responses to the workshop activities carried out, the average teacher gave positive responses.